Updating the approaches to define susceptibility and resistance to anti-tuberculosis agents: implications for diagnosis and treatment - Georghiou, Sophia B.; Rodwell, Timothy C.; Korobitsyn, Alexei; Abbadi, Said H.; Ajbani, Kanchan; Alffenaar, Jan-Willem; Alland, David; Alvarez, Nataly; Andres, Sönke; Ardizzoni, Elisa; Aubry, Alexandra; Baldan, Rossella; et al. (The European respiratory journal, 2022)
Tweetable abstract ERSpublications - click to tweetInappropriately high breakpoints have resulted in systematic false-susceptible AST results to anti-TB drugs. MIC, PK/PD and clinical outcome data should be combined when setting breakpoints to minimise the emergence and spread of antimicrobial resistance. https://bit.ly/3i43wb6